Chronic kidney disease and its association with cataracts–A cross-sectional and longitudinal study - Huang, Chun-Yen; Lee, Jia-In; Chang, Chia-Wen; Liu, Yao-Hua; Huang, Shu-Pin; Chen, Szu-Chia; Geng, Jiun-Hung (Frontiers in Public Health, 2022)
We aim to explore the association between chronic kidney disease (CKD) and cataracts. A total of 121,380 participants with adequate information collected from 29 community-based recruitment centers since 2008 were analyzed. The association between CKD and self-reported diagnosed cataracts was examined in a cross-sectional cohort and was validated in a longitudinal cohort of 25,263 participants without cataracts at baseline. Of all participants, cataracts occurred in 503/1,947 (26%) and 10,464/119,433 (9%) subjects in the CKD and non-CKD groups, respectively. Multivariate logistic regression showed that CKD was significantly associated with a higher prevalence of self-reported diagnosed cataracts. In the validation cohort, a higher incidence of cataracts was also noted in the CKD group (65/317, 21%) compared to the non-CKD group (1,964/24,252, 8%) during a mean 47-month follow-up. After adjusting for confounders, subjects with CKD had a 1.498-fold higher risk of incident cataracts than those without CKD (95% confidence interval = 1.114 to 2.013, p value = 0.007). We found that CKD was associated with a higher prevalence of cataracts as well as incident cataracts, which suggests CKD patients and their primary physicians should be aware of this disease and can provide a clue for further exploration of the possible mechanisms and treatments.